x2 - 4x - 21 = (x-7)(x+3)
4x2 - x - 3 = 0 (x - 1)(4x + 3) = 0 So x - 1 = 0 or 4x + 3 = 0 ie x = 1 or = -3/4 = -0.75
4x + 20
x(4x-2)
x2-4x-165 = (x-15)(x+11) when factored
x2 - 4x - 21 = (x-7)(x+3)
4x2 - x - 3 = 0 (x - 1)(4x + 3) = 0 So x - 1 = 0 or 4x + 3 = 0 ie x = 1 or = -3/4 = -0.75
8x2-10x-3 = (2x-3)(4x+1) when factored
4x + 20
x(4x-2)
It is a quadratic expression
x2-4x-165 = (x-15)(x+11) when factored
4(x - 1)(x + 1)
x2-10 = 4x+11 x2-4x-10-11 = 0 x2-4x-21 = 0 (x+3)(x-7) = 0 x = -3 and x = 7
x^2-4x/x^2-6x+8 = x(x-4)/(x-2)(x-4) = x/(x-2)
x - 2
Dividend: x3+4x2-9x-36 Divisor: x+3 Quotient: x2+x-12